The practice of Islamic taxation in Kazakhstan - Burnasheva, V.R. (BUKETOV BUSINESS REVIEW, 2024)
Object: to study the experience of Islamic taxation and identifying possible ways of its application in improving the taxation system of the Republic of Kazakhstan. Methods: Application of the method of generalization allowed to study the material consistently and build the overall structure of the study, the method of interpretation and comparison contributed to the evaluation of the scientists' positions and determination of the features of the development of Islamic taxation, which in comparison are comparable to the practice of development of the Kazakhstani taxation. Findings: The presented interpretations and attitudes of Islamic taxation are interpreted on the modern system of taxation of the Republic of Kazakhstan. The comparative analysis of the Islamic system of taxation and the modern system of taxation of Kazakhstan was carried out. It was established that musharaka can act as a method of financing financial processes, and in taxation it implies a platform of interaction between the public revenue authority and the taxpayer. The essence of the risk management system and the necessity of its application in taxation were revealed. a set of tasks of Islamic taxation contributing to the strengthening of the system of taxation of the Republic of Kazakhstan was developed and recommended. Conclusions: The results of the study confirmed that the Islamic system of taxation and the modern system of taxation of Kazakhstan have similar principles of taxation, with the application of the proposed set of tasks of Islamic taxation based on the Eisenhower matrix can affect the improvement of the indicators of the taxation system of the Republic of Kazakhstan in the future.